(untitled) (World Bulletin of Management and Law, 2022)
Budgeting is the main artery of the government, because the government performs all its financial functions for the implementation of its various programs within the framework of the budget law. On the other hand , people have the right to know how and for what purposes public funds are used. Be. In this regar the purpose of this study is the impact of government accounting systems and budgeting on government accountability. The present research is of applied type and belongs to the category of descriptivecorrelational research. The statistical population of the study includes the staff of the audit and accounting department and managers in government organizations in Al-Diwaniyah province in Iraq. The statistical sample size is 113 and 100 questionnaires were received. In this research, the standard Yousef questionnaire (2021) has been used to collect information. Data analysis was performed using spss and pls. The results of data analysis showed that there is no significant relationship between government accounting systems and government accountability and there is a significant relationship between government budgeting and accountability and also between government accounting systems and budgeting on accountability. Government There are no significant relationships .